PELAKSANAA PEMBINAAN NARAPIDANA WANITA YANG MENYUSUI DI LEMBAGA PERMASAYARAKATAN KELAS IIA PAMEKASAN - Husnul Hotimah (Dinamika, 2019)
Abstract    The results of this study indicate that every female prisoner who is pregnant and lactating has performed well even though in the Implementation Process of Guiding Prisoners of pregnant and lactating women also have problems in the Class IIA Correctional Institution Pamekasan. Class IIA Correctional Institutions also seek efforts to overcome obstacles that are in accordance with Government Regulation Number 32 of 1999. the existence of monitoring and evaluation by the Head of the Class IIA Correctional Institution Pamekasan so as to minimize any obstacles that occur in the implementation of Guiding Prisoners for pregnant and lactating women